NanoMarine therapeutics: a new wave in drug delivery from oceanic bioresources targeting colon cancer via miRNA modulation - Muthu, Ramkumar; Manickam, Rajkumar; Thamarai, Rajkumar; Sivasamy, Sivabalan; Mahendran, Karthikeyan; Prabhakaran, Rajkumar (Frontiers in Genetics, 2025)
The increasing global incidence of colorectal cancer (CRC) necessitates the development of innovative and targeted therapeutic interventions. Marine-derived bioactive compounds have gained prominence due to their structural diversity, intrinsic bioactivity, and potential to modulate oncogenic and tumor-suppressive microRNAs (miRNAs). Simultaneously, miRNAs have gained attention as critical regulators of gene expression in CRC, influencing key processes such as proliferation, metastasis, apoptosis, and chemoresistance. Nanotechnology has further transformed this field by enhancing drug solubility, stability, and tumor-specific delivery, thereby enabling combinatorial approaches such as the co-delivery of miRNA-targeted nano-formulations with conventional chemotherapeutics. Notably, co-delivery systems combining miRNA-targeted nano-marine drugs with conventional chemotherapy have shown synergistic effects in overcoming drug resistance and enhancing therapeutic efficacy. Despite encouraging preclinical outcomes, clinical translation remains constrained by challenges related to pharmacokinetics, scalability, immunogenicity, and regulatory compliance. This review critically evaluates the mechanistic interplay between marine compounds and miRNAs in CRC, advances in nanoformulation strategies, and translational barriers, providing insights into future directions for clinical application.